Study of Startups in the cloud to innovate agricultural production in Ecuador (IoT, data in the cloud) - Martínez Campoverde, Darwin José; Vega Abad , Cesar Remigio (Journal of business and entrepreneurial studie, 2023)
In Ecuador, startups have had a remarkable growth in the last decade due to the extensive amount of benefits they offer by using current technologies in the provision of a service or within production processes such as in agriculture, therefore it is considered necessary to describe them and show what systems they use in favor of innovation and increased agricultural production. Within this document, documentary research will be used to collect information, describe the current situation in Ecuador in this area, demonstrate the benefits that IoT and the use of Big-Data can mean.